A comparative study of different methods for isolating chitin from tiger shrimp (Penaeus monodon) carapace - Ong, Rachel Arcilla
This study involved a comparative study of three methods for isolating chitin from the carapace of tiger shrimp (Penaeus monodon). The carapace material was found to contain 40.80% moisture, 1.52% crude fat (db) 4.61% total crude nitrogen (db), 28.80% crude protein, 2.57% chitin nitrogen, 37.25% chitin, 2.04% corrected nitrogen, 12.75% corrected protein and 35.42% ash (db). Method 1, used previously for lobster shells, was modifies using decreased concentrations pf acid and alkali. Deproteinization using 50 g/l NaOH solution for three days at ambient temperature and demineralization using 32% HCl solution at -20°C for four hours, was selected as the most effective and least costly treatment for Method 1. Method 2 employed deproteinization using 1.0N NaOH at 100°C for 1 hour with a solids to solvent ration of 1:6, followed by demineralization with 1.25N HCl at ambient temperature for 30 minutes and a 1:12 solids to solvent ratio. Method 3 was accomplished through demineralizing first with 1.0N HCl for 30 minutes at ambient temperature with 1:15 solids to solvent ratio, then deproteinizing with 3.5% NaOH for two hours at 65°C with a solids to solvent ratio of 1:10. The chitin isolated using Method 1 has a bone ivory color, coarse, grainy texture, with 41.42% chitin yield, 3.40% moisture, 49.58% ash and 2.73% crude nitrogen contents. Isolation Method 2 yielded a lily white and flaky chitin with 28.69% chitin yield, 2.88% moisture, 0.088% ash and 5.78% crude nitrogen contents. All the chitin samples from the different methods exhibited insolubility in water, dilute acid and alkali, and partial to complete solubility in concentrated acid. Comparative cost analysis results for the production of a kilogram of chitin were P1842.38 for Method 1, P1305.92 for Method 2 and P1465.15 for Method 3. Method 2 was found to be the most economically feasible.